Prognostic impact of isolated right ventricular dysfunction in sepsis and septic shock: an 8-year historical cohort study - Saraschandra Vallabhajosyula; Mukesh Kumar; Govind Pandompatam; Ankit Sakhuja; Rahul Kashyap; Kianoush Kashani; Ognjen Gajic; Jeffrey B. Geske; Jacob C. Jentzer (Annals of Intensive Care, 2017)
Abstract Background Echocardiographic myocardial dysfunction is reported commonly in sepsis and septic shock, but there are limited data on sepsis-related right ventricular dysfunction. This study sought to evaluate the association of right ventricular dysfunction with clinical outcomes in patients with severe sepsis and septic shock. Methods Historical cohort study of adult patients admitted to all intensive care units at the Mayo Clinic from January 1, 2007 through December 31, 2014 for severe sepsis and septic shock, who had an echocardiogram performed within 72 h of admission. Patients with prior heart failure, cor-pulmonale, pulmonary hypertension and valvular disease were excluded. Right ventricular dysfunction was defined by the American Society of Echocardiography criteria. Outcomes included 1-year survival, in-hospital mortality and length of stay. Results Right ventricular dysfunction was present in 214 (55%) of 388 patients who met the inclusion criteria—isolated right ventricular dysfunction was seen in 100 (47%) and combined right and left ventricular dysfunction in 114 (53%). The baseline characteristics were similar between cohorts except for the higher mechanical ventilation use in patients with isolated right ventricular dysfunction. Echocardiographic findings demonstrated lower right ventricular and tricuspid valve velocities in patients with right ventricular dysfunction and lower left ventricular ejection fraction and increased mitral E/e′ ratios in patients with combined right and left ventricular dysfunction. After adjustment for age, comorbidity, illness severity, septic shock and use of mechanical ventilation, isolated right ventricular dysfunction was independently associated with worse 1-year survival—hazard ratio 1.6 [95% confidence interval 1.2–2.1; p = 0.002) in patients with sepsis and septic shock. Conclusions Isolated right ventricular dysfunction is seen commonly in sepsis and septic shock and is associated with worse long-term survival.